Investigation of experimental observables in search of the chiral magnetic effect in heavy-ion collisions in the STAR experiment *Supported by the US Department of Energy (DE-AC02-98CH10886, DE-FG02-89ER40531, DE-FG02-92ER40713, DE-FG02-88ER40424, DE-SC0012910, DE-SC0013391, DE-SC0020651), and the National Natural Science Foundation of China (12025501, 11905059, 12075085), the Strategic Priority Research Program of Chinese Academy of Science with (XDB34030200), the Fundamental Research Funds for the Central Universities (CCNU19ZN019), the Ministry of Science and Technology (MoST) (2016YFE0104800) and the China Scholarship Council (CSC), Join Large-Scale Scientific Facility Funds of NSFC and CAS (U2032110), the U.S. Department of Energy, Office of Science, Office of Nuclear Physics, within the framework of the Beam Energy Scan Theory (BEST) Topical Collaboration, the U.S. National Science Foundation (PHY-1913729), the Natural Sciences and Engineering Research Council of Canada, the Fonds de recherche du Québec - Nature et technologies (FRQNT) through the Programmede Bourses d'Excellencepour Étudiants Étrangers (PBEEE). (January 2022) - Choudhury, Subikash; Dong, Xin; Drachenberg, Jim; Dunlop, James; Esumi, ShinIchi; Feng 冯, Yicheng 毅程; Finch, Evan; Hu 胡, Yu 昱; Jia, Jiangyong; Lauret, Jerome; Li, Wei; Liao 廖, Jinfeng 劲峰; et al.
Abstract: The chiral magnetic effect (CME) is a novel transport phenomenon, arising from the interplay between quantum anomalies and strong magnetic fields in chiral systems. In high-energy nuclear collisions, the CME may survive the expansion of the quark-gluon plasma fireball and be detected in experiments. Over the past two decades, experimental searches for the CME have attracted extensive interest at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC). The main goal of this study is to investigate three pertinent experimental approaches: the correlator, the R correlator, and the signed balance functions. We exploit simple Monte Carlo simulations and a realistic event generator (EBE-AVFD) to verify the equivalence of the core components among these methods and to ascertain their sensitivities to the CME signal and the background contributions for the isobar collisions at the RHIC.